Preventing More 'Missing Girls' : A Review of Policies to Tackle Son Preference - Kumar, Sneha (World Bank, Washington, DC, 2018)
In parts of Asia, South Caucasus, and the Balkans, son preference is strong enough to trigger significant levels of sex selection, result in the excess mortality of girls, and skew child sex ratios in favor of boys. Every year, 1.8 million girls under the age of five go “missing” because of the widespread use of sex selective practices in these regions. The pervasive use of such practices is reflective of the striking inequities girls face today, and it also has negative implications for efforts to improve women's status in the long term. Consequently, governments of countries in these regions have employed direct measures, such as banning the use of prenatal sex selection technology and providing financial incentives to families that have girls. This paper takes stock of the direct measures used across countries grappling with skewed child sex ratios and compares the efficacy of direct measures with measures that indirectly raise the value of daughters. The stocktaking suggests that there is no conclusive evidence that direct approaches reduce the higher mortality risk for girls. Bans on the use of sex selection technology may inadvertently worsen the status of the very individuals they intend to protect, and financial incentives to families with girls offer short-term benefits at most. Alternatively, indirect measures, such as legal reform to promote gender equity and advocacy efforts, offer more promise by bringing about permanent shifts in the relative value of daughters. The stocktaking also underscores the paucity of causal studies in this literature.